Análisis del gasto militar desde la perspectiva de la economía de la defensa: El caso colombiano 1950-2006 (2020)
The present investigation centers its analysis in the cost of defense and security (GDS) using the use of the discipline of the defense economy, which studies the policies of security by means of the application of tools elaborated by the economy as they are the methods of macroeconomic and microeconomic analysis, static optimization - dynamic, theory of games and Econometry. The interest by the study of the defense and the security is recent and has received height due to the insertion of Colombia in the international scene, because of the internal conflict that persists in the country, and that has gotten to be part of the international agenda. The sector defense has not had technocratic tradition, and the Investigation field is incipient, the present work presents/displays an approach to the study of the cost in defense and security (GDS) between 1950 - 2006, where it will be verified as this one macroeconomic aggregate stayed below the regional average through century XX. The GDS of this country is not correlated with the internal conflict and the trajectory that follows is random; the policy of security and defense is product of conjuncture events and not the fruit of a planning of the first public good that must give a State to its citizens, of this form the inference that this it has had on public property, does not respond to a state public policy.